Psychosocial Adjustment and Marital Intimacy Among Partners of Patients with Breast Cancer: A Comparison Study with Partners of Healthy Women - Moreira, Helena (2013)
This cross-sectional study investigated the psychosocial adjustment of 70 partners of patients with breast cancer by comparing their emotional adjustment and quality of life (QoL) with 70 partners of women without cancer. The role of marital intimacy in their adjustment and the moderating effect of group type were analyzed. The partners of patients with breast cancer presented higher levels of anxious and depressive symptomatology; poor social, psychological, general and physical QoL; and higher levels of intimacy. The moderation analysis showed that higher levels of intimacy predicted lower levels of depression and anxiety and greater QoL only among the partners of cancer patients.